« There are kisses for all » : Le defilé des jeunes hommes - Luc Bouvard (Cahiers Victoriens et Edouardiens)
This paper yields what others refrain from doing, i.e. provide the reader with part of the donkey work that is obviously necessary whenever one means to tackle such a subject as the transformation processes at work in the film adaptation of a novel. The initial title of Coppola’s film version of Bram Stoker’s novel, Dracula : the Untold Story, was probably closer to the finished product. However, the film director chose to claim his film adaptation as the most faithful rendition on screen of the famous gothic novel. Everyone knows fidelity is not the most appropriate word when one deals with this film, owing to the essential addition made by the screenwriter James V. Hart, namely the love story across the ages between Dracula the Un-Dead and Mina, the reincarnation of Princess Elizabeta. In spite of this new strand in the plot, Coppola claims his film is as close to the novel as can be. Through a constant reference to the table concerned with the diegetic elements that the filmmaker chose to transfer or not to transfer, conflate or dilate, displace or suppress, I have endeavoured to systematize Brian McFarlane’s methodology. Partly borrowed from Roland Barthes’s structuralist approach, McFarlane’s method of analysis is based on the Barthesian premise that a diegesis is composed of four elements : cardinal functions, catalysers, informants and indices proper. He suggested that only the first three could be easily transferred and that the last one required adaptation proper. The table supplied with this paper draws a constant comparison between the novel and the film for the three items that can undergo a transfer procedure. Thanks to this systematic confrontation, the paper draws a few conclusions, concerning a group of characters, commonly called the crew of light, their functions (cardinal and catalysers) and their informants (names, ages and physical characteristics). This paper mainly focuses on the younger characters in this party : Seward, Morris, Holmwood and Harker.